2015
DOI: 10.1016/j.alit.2015.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Omalizumab in Japanese children with severe allergic asthma uncontrolled with standard therapy

Abstract: In Japanese children with severe allergic asthma, omalizumab decreased free IgE levels to less than 25 ng/mL. Omalizumab improved asthma control and was well-tolerated, as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 28 publications
5
20
0
1
Order By: Relevance
“…In two double-blind, randomized, placebo-controlled trials (RCTs) of children aged 6 to 12 years with moderate-to-severe allergic asthma, treatment with omalizumab reduced the requirement for ICS and protected against disease exacerbations, but there was little change in asthma symptom scores or spirometry [ 9 , 64 ]. These findings were confirmed and extended in older children [ 65 67 ].…”
Section: Discussionsupporting
confidence: 54%
“…In two double-blind, randomized, placebo-controlled trials (RCTs) of children aged 6 to 12 years with moderate-to-severe allergic asthma, treatment with omalizumab reduced the requirement for ICS and protected against disease exacerbations, but there was little change in asthma symptom scores or spirometry [ 9 , 64 ]. These findings were confirmed and extended in older children [ 65 67 ].…”
Section: Discussionsupporting
confidence: 54%
“… Clinically relevant (> 0.5 point) improvement from baseline in the AQLQ and mini-AQLQ scores in 67.2% of patients at month 12 and 60.7% at month 24. Odajima et al, 2015 [ 53 ] multicenter, uncontrolled, open label study Children (6–15 years) with uncontrolled severe allergic asthma ( n = 38) Improved scores of asthma-specific QOL questionnaire for pediatric patients after 24 weeks. Li et al, 2016 [ 54 ] RDBPC, parallel-group, phase III study Patients ≥18 years with uncontrolled moderate-to-severe persistent allergic asthma ( n = 616) Improved overall AQLQ scores and all individual domain scores after 24 weeks.…”
Section: Biologics In Severe Asthmamentioning
confidence: 99%
“…In 2 randomized controlled studies of omalizumab, FEV 1 in the omalizumab arm was no better than with the placebo at 24 weeks [8] or 48 weeks [9]. Real-world studies of omalizumab reported that it improved FEV 1 from the baseline at 24 weeks [10] and at 1 year [11], but not at 2 years [12]. For mepolizumab, because of the low prevalence of severe eosinophilic asthma in adolescents, a subgroup analysis of 4 phase II/III mepolizumab trials was recently reported [13].…”
Section: Discussionmentioning
confidence: 99%